Physical and Socio-Economic Environmental Consequences of Brick Industry: A Case Study of Domohani Village: Examining the impacts of brick industry on Domohani Village (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Economic development of a society depends on industrialization either it’s a town, city, state or a country .when we talking about modern industrialized fully concrete urbanized state at that time the importance of brick factory is highlight. Contribution of brick factory to the industrial development or in the establishment of modern society is highly appreciable. Brick factories play a complex role in socio economic development, but there are some of its most important effect sometimes it may be positive or sometime they are responsible for some adverse effect to the society also. The paper basically deals with the physical and socio economic consequence of brick industry of Domohani village of Barabani block and try to suggest a better alternative plan for solution related with the industry.